Unconscious errors enhance prefrontal-occipital oscillatory synchrony - Cohen, Michael X.; Van Gaal, Simon; Ridderinkhof, K. Richard; Lamme, Victor (Frontiers in Human Neuroscience, 2009)
The medial prefrontal cortex (MFC) is critical for our ability to learn from previous mistakes. Here we provide evidence that neurophysiological oscillatory long-range synchrony is a mechanism of post-error adaptation that occurs even without conscious awareness of the error. During a visually signaled Go/No-Go task in which half of the No-Go cues were masked and thus not consciously perceived, response errors enhanced tonic (i.e., over 1–2 s) oscillatory synchrony between MFC and occipital cortex (OCC) leading up to and during the subsequent trial. Spectral Granger causality analyses demonstrated that MFC → OCC directional synchrony was enhanced during trials following both conscious and unconscious errors, whereas transient stimulus-induced occipital → MFC directional synchrony was independent of errors in the previous trial. Further, the strength of pre-trial MFC-occipital synchrony predicted individual differences in task performance. Together, these findings suggest that synchronous neurophysiological oscillations are a plausible mechanism of MFC-driven cognitive control that is independent of conscious awareness.